'In Gilbert and Sullivan Land' (Operetta) - Part of Josephine (reverse) - Unknown (Tufts Archival Research Center, 2014)
5.2 x 8.2 in., photographic print. Back of photograph showing Muriel Simonson wearing a kimono while playing the part of Josephine in 'In Gilbert and Sullivan Land,' a play produced at Tufts in February, 1929.